Renal features of Bardet Biedl syndrome: A single center experience - Atmış, Bahriye; Karabay-Bayazıt, Aysun; Melek, Engin; Bişgin, Atıl; Anarat, Ali (The Turkish Journal of Pediatrics, 2019)
Bardet Biedl syndrome (BBS), is a multisystemic disorder which is described as a ciliopathy. BBS is a rare autosomal recessive disorder and 21 different BBS genes have been defined to date. BBS is characterized with dysmorphic extremities, retinitis pigmentosa, obesity, hypogenitalism, intellectual disabilility and renal structural abnormalities. Renal symptoms in patients with BBS, are nonspecific and often undetected until end-stage renal disease. Here, we were reported 23 children with BBS (12 females, 11 males) with renal abnormalities from a single center and defined their features. Age at diagnosis were very variable (2 days-16 years). Median age at diagnosis was 84 months. Mean follow-up period was 42 months. All 23 children had urinary tract abnormalities on renal ultrasonography. These abnormalities were polycysts (34.8%), hyperechogenic kidneys (34.8%), fetal lobulation (21.7%), hypoplasia on at least one kidney (21.7%) and hydronephrosis in at least one kidney (17.4%). Vesicoureteral reflux and neurogenic bladder detected 11.1% and 22.2% of patients who recieved a voiding cystourethrogram, respectively. Proteinuria was found in 39 % of patients. Hypertension was defined in 21.7% of patients. Six of 23 children (26%) in our cohort had proven mutations in BBS genes. Five of them (83.3%) had homozygous mutations in BBS10 gene and one of them had homozygous mutation in BBS2 gene. All of 23 children had retinitis pigmentosa, twenty two of them (95.6%) had learning disabilities/cognitive impairment and seventeen of them (82.6%) had obesity. Renal involvement is now accepted as a cardinal feature and the most important factor causing mortality in BBS.